1999
DOI: 10.1097/00005537-199905000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of meniere disease in finland

Abstract: The prevalence and incidence in Finland is lower than could be expected from previous international surveys, most of which provide inadequate data for forming a real picture of the epidemiology of Meniere disease. Uniform diagnostic criteria are indispensable for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 14 publications
(20 reference statements)
0
57
0
5
Order By: Relevance
“…In Finland, an extrapolated prevalence estimate of 0.43 per 1,000 was reported 8 . The Swedish figure 9 of 0.46 per 1,000 (circa 1 in 2000), coming from a well-documented homogeneous population, seems the most acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…In Finland, an extrapolated prevalence estimate of 0.43 per 1,000 was reported 8 . The Swedish figure 9 of 0.46 per 1,000 (circa 1 in 2000), coming from a well-documented homogeneous population, seems the most acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…The Rochester study reported a prevalence of 218 per 100,000 population in 1984; 19 the Southern Finland study reported 513 per 100,000 population in 1999. 20 We found no impact of occupation on dizziness. In our population, dizziness was equally distributed among employed and unemployed within all types of jobs.…”
Section: Medicalexpress (São Paulomentioning
confidence: 52%
“…Para além dos fatores já referidos anteriormente, que levam à dificuldade em se determinar com precisão os dados epidemiológicos, também os conceitos de prevalência e incidência foram abordados das mais variadas formas ao longo dos anos. 13 Um dos primeiros estudos publicados sobre epidemiologia da DM foi conduzido em Inglaterra por Cawthorne e Hewlett, onde apresentam uma série de 900 casos identificados com DM. No entanto, tendo em consideração que com base na sua amostra não chegariam a um valor real da incidência da DM, baseiam-se nos registos mé-dicos de oito clínicas, entre março de 1953 e março de 1954, abrangendo uma população de 27 365 habitantes e encontram 43 casos de DM, obtendo assim uma incidência de 15 714 casos por 100 000 habitantes.…”
Section: Prevalência E Incidênciaunclassified
“…3 Da Finlândia surgem dois estudos que apresentam prevalências tão díspares como 43,2 casos por 100 000 habitantes num e 513 casos por 100 000 habitantes no outro. 13,15 Estes resultados poderiam ser explicados com base nas diferenças geográficas e étnicas que podem existir dentro de um mesmo país mas, quando se analisam com detalhe ambos os estudos, percebemos que estas diferenças se devem essencialmente às diferentes metodologias aplicadas em cada um dos estudos. 16 Ambos os estudos são analisados por Radtke et al No primeiro estudo, acreditam que a verdadeira prevalência é presumivelmente mais alta, tendo em conta que muitos casos de DM não estão refletidos no estudo.…”
Section: Prevalência E Incidênciaunclassified
See 1 more Smart Citation